EFFORTS TO HANDL PULMONARY TUBERCULOSIS IN A 72-YEAR-OLD MALE PATIENT THROUGH A FAMILY MEDICINE APPROACH AT THE NISAM PUBLIC HEALTH CENTER, NORTH ACEH DISTRICT - Abi Pulungan (Jurnal Medika Hutama, 2026)
Patient Mr. MY visited the infectious disease clinic at the Nisam Community Health Center complaining of a productive cough that had persisted for the past two months. The cough was experienced continuously every day, with phlegm that was difficult to clear despite the patient’s attempts at self-treatment. Since the onset of symptoms, the cough had shown no improvement; in fact, it tended to persist and increasingly interfered with the patient’s daily activities. Primary data were obtained through self-reported history and physical examination, including a home visit, completion of the family folder, and completion of the patient’s medical record. Assessment was conducted based on a holistic diagnosis at the beginning, during, and end of the visit, using both quantitative and qualitative methods. Interventions included educating the patient about pulmonary TB, lifestyle modifications, and disease management, as well as explaining potential complications of the patient’s condition to encourage regular treatment and preventive measures.